Best Pensions with Most Representative Actuarial Mathematical Models - Cavero Vicentelo, José E. (2018)
In Peru and in the world there is a great scientific, technological, knowledge, accumulation of capital, etc. evolution. in the face of an increasing inequality, a fall in the proportion of salaries with respect to income, tax evasion is avoided in tax havens, replacement of human resources by technology, etc. and generally small pensions are estimated, accentuating inequality, thinking that in Peru for example, a person of 65 years will live 45 years more until 110 years.It is proposed to improve the pension, by interrelated model concepts and actuarial balance with life expectancy at the time of acquiring the right, achieving greater representation. The most probable age of death is estimated by life expectancy, defined as the number of years that, on average, the person still has to live according to age and sex upon cessation or acquisition of rights, with results of up to more than 25%. with the current tables, a 65-year-old man or woman will probably live 17 or 22 years more and not 45 years more.